Diagnóstico da qualificação dos servidores federais para o desenvolvimento de competências ao cumprimento dos objetivos de desenvolvimento sustentável - Elias, Renata Bernardes (2021)
Sustainability is a reality in the changes of contemporary society. In this context, universities and other public sectors assume a strategic role in offering excellent services and quality of life to users. One of the obstacles in this process is the lack of qualification and sensitization of civil servants about their social responsibility and mobilizing role in sustainable development. Competences to achieve SDG are gaps as a vector for Sustainable Development in Public Management. Thus, this paper aims to assess the level of qualification of UFU’s servants to achieve 2030 Agenda based on competences for sustainability proposed in the literature. The methodological qualitative and quantitative approach were used by a survey with the civil servants of the Federal University of Uberlândia. The quantitative approach based on statistical analysis and the qualitative study used codes, category analysis, and document analysis, generating an experience report. As a technological product, a diagnosis was prepared and from this it is possible to conclude that there is a need for qualification of civil servants to achieve 2030 Agenda, in terms of knowledge, skills and attitudes. Therefore, developing competences is a need despite recognizing the benefits of complying with the SDGs in the Institution. The paper has practical implications to integration of sustainability assumptions in Public Administration, in addition, it supports advances in the theory of competences applied to sustainable development, with specific application in the public sector.